Estudo fitoquímico da Paliavana tenuiflora Mansf. (GESNERIACEAE) - Silva, Evandro Ferreira da (2014)
The genus Paliavana. belongs to Gesneriaceae family and is composed of about 140 species distributed in all South and Central America (except Caribbean and Mexico). In Brazil are found in the Southeast region of Espírito Santo, Minas Gerais and Rio de Janeiro and Northeast region Bahia, Paraíba, Pernambuco . Occurs on rocky outcrops of high altitude grasslands, called "rock fields", these are represented by herbs and shrubs. Paliavana tenuiflora is found in rain forests on rocky outcrops in Paraíba, Pernambuco, Bahia and Minas Gerais, there are no reports of phytochemical study of this species. Thus, this study aimed to contribute to the phytochemical study of Paliavana tenuiflora Mansf . Plant material was material was collected in Pedra de Santo Antônio of Paraíba- Galante and deposited in the Herbarium Prof. Lauro Pires Xavier (JPB) under code M.F. Agra, 6090. For the phytochemical study, aerial parts of plant were subjected to extraction processes, partition and chromatography for chemical constituents isolation. Chemicals structures of the compounds has been assessed by spectroscopic methods such as IR, mass and nuclear magnetic resonance 1H and 13C two-dimensional and comparisons with literature data. From ethyl acetate phase was obtained a mixture of glycosylated steroids (sitosterol -3-O-D- glucopyranoside and stigmasterol-3-O-Dglucopyranoside) and tree phenolic compounds, hexacosanoic acid 2-(phydroxyphenyl)- ethyl ester, hexacosanoic acid 2-(3, 4-dihydroxyphenyl) - ethyl ester beyond acid 3-(3,4-dihydroxyphenyl) prop-2-enoic (caffeic acid), being this two esters reported for the first time in the genus thus contributing to the chemical study of the genus Paliavana.